2011
DOI: 10.1111/j.1365-2966.2011.19243.x
|View full text |Cite
|
Sign up to set email alerts
|

The OGLE view of microlensing towards the Magellanic Clouds - IV. OGLE-III SMC data and final conclusions on MACHOs★

Abstract: In this fourth part of the series presenting the Optical Gravitational Lensing Experiment (OGLE) microlensing studies of the dark matter halo compact objects (MACHOs), we describe results of the OGLE‐III monitoring of the Small Magellanic Cloud (SMC). Three sound candidates for microlensing events were found and yielded the optical depth τSMC‐OIII= 1.30 ± 1.01 × 10−7, consistent with the expected contribution from Galactic disc and SMC self‐lensing. We report that event OGLE‐SMC‐03 is most likely a thick‐disc … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
190
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 37 publications
6
190
0
2
Order By: Relevance
“…In the LIGO region, microlensing (Alcock et al 1996Allsman et al 2001;Lasserre 2000;Tisserand et al 2007;Wyrzykowski et al 2011) and star cluster dynamics in the Eridanus II (Brandt 2016) and Segue I dwarf galaxies (Koushiappas & Loeb 2017) place the tightest constraints on PBH dark matter (Fig. 1).…”
Section: An Overview Of Constraints On Primordial Black Hole Dark Mattermentioning
confidence: 99%
“…In the LIGO region, microlensing (Alcock et al 1996Allsman et al 2001;Lasserre 2000;Tisserand et al 2007;Wyrzykowski et al 2011) and star cluster dynamics in the Eridanus II (Brandt 2016) and Segue I dwarf galaxies (Koushiappas & Loeb 2017) place the tightest constraints on PBH dark matter (Fig. 1).…”
Section: An Overview Of Constraints On Primordial Black Hole Dark Mattermentioning
confidence: 99%
“…There is a window for PBHs to be DM if the BH mass is in the range 20 M M 100 M [8,9]. Lower masses are excluded by microlensing surveys [10][11][12]. Higher masses would disrupt wide binaries [9,13,14].…”
mentioning
confidence: 99%
“…The observational result from this lensing is the magnification of light of the source object (Paczyński 1986). This method has been used for detection of possible MACHOs 1 in the Galactic halo and the observations of EROS, MACHO and OGLE groups for almost one decade in the direction of Large Magellanic Clouds revealed that MACHOs do not contribute in the dark matter budget of Galactic halo (Tisserand et al 2007;Wyrzykowski et al 2011;Moniez 2010). Also in recent years this method is used as a strong tool for detection of Earth-mass extrasolar planets beyond the snow line (Mao & Paczynski 1991;Gould et al 2010;Gaudi 2012).…”
Section: Introductionmentioning
confidence: 99%